Rehabilitation of Nose following Chemical Burn Using CAD/CAM Made Substructure for Implant Retained Nasal Prosthesis: A Clinical Report. (18th June 2017) - Chaturvedi, Saurabh; Bhagat, Tushar; Verma, A. K.; Gurumurthy, Vishwanath; Ali, Mariyam; Vadhwani, Preeti; Chaturvedi, Mudita
Abstract : Insufficient knowledge of medical chemicals and their improper use have destructive effects. Accidental exposure to chemicals on facial tissue may result in large facial defect. For ages the tradition of piercing nose is common but improper use of unknown chemical for piercing has deleterious effect. Mostly rhinectomy defects are acquired caused by trauma or malignant diseases. Prosthetic rehabilitation is the preferred treatment of choice for any large rhinectomy defects as medical and surgical interventions are ineffective in developing esthetics. Main concern with the prosthesis for such defects is retention. This article describes rehabilitation of a patient with large size nasal defect created by chemical burn in childhood during piercing. Implant retained customized silicone nasal prosthesis was fabricated using simple O-ring attachments and innovative modified polyamide acrylic resin substructure acting as skeleton.